Battery cell, battery device, and electric device
By using a high graphitization negative electrode material in the battery and combining with lithium bisfluorosulfonimide electrolyte, combining the ratio of chain carboxylate and carbonate solvents, as well as ceramic coating and multi-pole ear designs, It solves the problems of fast charging, cycle life and safety performance of the battery, and achieves the improvement of high temperature stability and safety of the battery.
Patent Information
- Application Number
- CN202411606713.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-17
AI Technical Summary
Existing battery technology is difficult to take into account fast charging performance, cycle life and safety performance, especially in high temperature conditions, which frequently side reactions affect the stability and safety of the battery.
The negative electrode active material with a graphitization degree of 90%-96% combined with an electrolyte containing lithium difluorosulfonimide is used to optimize the lithium ion transfer rate through the ratio of chain carboxylate solvents and carbonate solvents. Matching with liquid phase transfer rates, reduce side reaction frequency, and improve mechanical strength and thermal management through ceramic coating and multipole ear design.
It achieves the balance of fast charging performance, cycle life and safety performance of the battery cell, improves the high temperature stability and safety of the battery, and extends the service life of the battery.
Smart Images

Figure CN119153759A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a battery cell, a battery device and an electrical device. Background Art
[0002] In recent years, battery monomers have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] With the market's increasing demand for fast charging performance, cycle performance and safety performance of battery cells, how to achieve a comprehensive improvement in battery performance at the same time has become a technical problem that urgently needs to be solved in this field. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a battery cell having both good fast charging performance and safety performance.
[0005] In a first aspect, the present application provides a battery cell, which comprises a positive electrode plate, a negative electrode plate, an electrolyte and a separator arranged between the positive electrode plate and the negative electrode plate; the electrolyte comprises a solvent and an electrolyte salt, the electrolyte salt comprises lithium bis(fluorosulfonyl)imide, and the mass proportion of the lithium bis(fluorosulfonyl)imide based on the total mass of the electrolyte is 1%-6%; the solvent comprises a chain carboxylate solvent, and the mass proportion of the chain carboxylate solvent based on the total mass of the electrolyte is 5%-75%; the negative electrode plate comprises a negative electrode collector and a negative electrode film layer arranged on at least one side of the negative electrode collector, the negative electrode film layer comprises a negative electrode active material, and the degree of graphitization of the negative electrode active material is 90%-96%; the positive electrode plate comprises a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode collector comprises an aluminum foil, and the thickness of the aluminum foil is 10μm-16μm.
[0006] During the research process, the applicant found that the negative electrode active material with a graphitization degree within the above range is combined with an electrolyte containing a chain carboxylic acid ester solvent and lithium bis(fluorosulfonyl)imide, which can not only reduce the probability of side reactions between the electrolyte and the defect sites of the negative electrode active material at high temperature, but also reduce the degree of side reactions between lithium bis(fluorosulfonyl)imide and the negative electrode active material with deep lithium embedding. It can also form a match between the solid-liquid transfer rate of lithium ions and the liquid phase transfer rate through a certain degree of disorder of the negative electrode active material and the chain carboxylic acid ester solvent, thereby promoting the rapid insertion and removal of lithium ions in the negative electrode active material, and achieving a balance between the fast charging performance, safety performance and high-temperature cycle life of the battery cell.
[0007] In any embodiment, based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide is 1.5%-5%.
[0008] Based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide within the above range is beneficial to further improve the safety of the battery while maintaining good fast charging performance and high-temperature cycle life of the battery.
[0009] In any embodiment, based on the total mass of the electrolyte, the mass proportion of the linear carboxylate solvent is 10%-65%.
[0010] Based on the total mass of the electrolyte, a mass proportion of the chain carboxylic acid ester solvent within the above range is beneficial for taking into account both the fast charging performance and high temperature cycle life of the battery monomer.
[0011] In any embodiment, the graphitization degree of the negative electrode active material is 92%-95%.
[0012] In any embodiment, based on the total mass of the electrolyte salt in the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is 10%-50%.
[0013] When the mass proportion of lithium bis(fluorosulfonyl)imide in the electrolyte salt of the electrolyte is within the above range, it can not only reduce the amount of chain carboxylic acid ester solvents used to a certain extent, but also reduce the production of hydrogen fluoride in the high-temperature cycle of the battery, and can also alleviate the degree of reaction with the negative electrode active material deeply embedded with lithium, and work together to improve the high-temperature cycle performance and safety performance of the battery monomer.
[0014] In any embodiment, the linear carboxylate solvent includes one or more of ethyl acetate, methyl acetate, methyl formate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, propyl butyrate, butyl butyrate, isopropyl acetate, and isoamyl acetate.
[0015] The above-mentioned chain carboxylate solvent molecules have higher lithium ion conductivity. Compared with other chain carboxylate solvents, only a small amount of addition is needed to achieve higher lithium ion conductivity. While improving the fast charging performance of battery cells, it can effectively control the degree of side reactions between the electrolyte and the negative electrode active material, allowing the battery cells to further improve the cycle stability while maintaining good fast charging performance.
[0016] In any embodiment, the chain carboxylate solvent includes one or more of ethyl acetate and methyl acetate. Based on the total mass of the solvent, the total mass of ethyl acetate and methyl acetate accounts for 5%-80%, and can be optionally 10%-70%.
[0017] Compared with other carboxylic acid ester solvents, ethyl acetate and methyl acetate have better kinetic activity and relatively low gas production levels, which are beneficial to further improve the lithium ion transmission rate and reduce the level of side reactions between the electrolyte and the negative electrode at high temperatures, while taking into account the fast charging performance and high-temperature cycle stability of the battery cells.
[0018] In any embodiment, the chain carboxylate solvent includes methyl acetate, and the mass content of methyl acetate is 5%-80%, optionally 5%-50%, and further optionally 10%-40%, based on the total mass of the solvent.
[0019] In any embodiment, the solvent further includes a carbonate solvent, and the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0020] In any embodiment, the solvent comprises ethylene carbonate, and the mass content of ethylene carbonate is 15%-35% based on the total mass of the solvent.
[0021] Ethylene carbonate has a high dielectric constant, which is beneficial to improve the solubility of lithium salts in the electrolyte, increase the lithium ion concentration in the electrolyte, improve the conductivity of the electrolyte, and improve the fast charging performance of the battery. At the same time, ethylene carbonate has good film-forming properties, which is beneficial to improve the quality of the SEI film on the surface of the negative electrode, reduce the degree of side reactions between carboxylic acid esters and the negative electrode, and improve the cycle life of the battery.
[0022] In any embodiment, the solvent comprises dimethyl carbonate, and the mass content of dimethyl carbonate is 5%-50% based on the total mass of the solvent.
[0023] Dimethyl carbonate has good electrical conductivity and gas production performance. Adding dimethyl carbonate to the electrolyte can appropriately reduce the content of carboxylic acid ester in the electrolyte, thereby reducing the degree of side reaction between carboxylic acid ester and the negative electrode, and improving the cycle life of the battery while maintaining the fast charging performance of the battery.
[0024] In any embodiment, the negative electrode current collector comprises copper foil, and the thickness of the copper foil is 4 μm-6 μm, and optionally 4 μm-5 μm.
[0025] When the thickness of the copper foil is within the above range, it can reduce the internal resistance of the battery and the heat generated by the battery cells during fast charging through a certain current collector thickness, so that the battery cells can withstand higher charging currents and improve the battery fast charging performance and safety performance; it can also increase the energy density of the battery by thinning the current collector, thereby taking into account both the fast charging performance and energy density of the battery cells.
[0026] In any embodiment, the single-side density of the negative electrode film layer is 0.08 g / 1540.25 mm2 -0.20g / 1540.25mm 2 , optional 0.10 g / 1540.25mm 2 -0.16 g / 1540.25 mm 2 .
[0027] A battery cell with a single side density of the negative electrode film layer within the above range can reduce the transmission distance of lithium ions in the negative electrode film layer, match with an electrolyte with high conductivity, reduce the concentration polarization generated by the battery cell during fast charging, and enable the battery cell to withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0028] In any embodiment, the compacted density of the negative electrode sheet is 1.2 g / cm 3 -1.9 g / cm 3 , optional 1.2 g / cm 3 -1.65g / cm 3 .
[0029] The negative electrode sheet with a compaction density within the above range has a suitable porosity, can match the electrolyte with high conductivity, increase the diffusion rate of lithium ions in the negative electrode, reduce the concentration polarization generated during fast charging, and enable the battery cell to withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0030] In any embodiment, the average thickness of a single side of the negative electrode film layer is 30 μm-150 μm, and optionally 30 μm-80 μm.
[0031] A battery cell with an average single-side thickness of the negative electrode film layer within the above range can reduce the transmission distance of lithium ions in the negative electrode film layer, match with an electrolyte with high conductivity, reduce the concentration polarization generated by the battery cell during fast charging, and enable the battery cell to withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0032] In any embodiment, the porosity of the negative electrode sheet is 20%-60%, and can be optionally 25%-40%.
[0033] The negative electrode plate with a porosity within the above range can be matched with an electrolyte with high conductivity, thereby increasing the diffusion rate of lithium ions in the negative electrode and reducing the concentration polarization generated by the battery cell during fast charging, so that the battery cell can withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0034] In any embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, and the positive electrode current collector includes aluminum foil, and the thickness of the aluminum foil is 10 μm-16 μm.
[0035] When the thickness of the aluminum foil is within the above range, it can reduce the internal resistance of the battery and the heat generation of the battery cells under high-rate charge and discharge through a certain current collector thickness, thereby improving the fast charging performance and safety performance of the battery; it can also increase the energy density of the battery by thinning the current collector, thereby taking into account both the fast charging performance and energy density of the battery cells.
[0036] In any embodiment, the thickness of the aluminum foil is 11 μm to 14 μm.
[0037] The thickness of the aluminum foil within the above range can further improve the current collector's current carrying capacity, alleviate the uneven current density distribution on the electrode and the inconsistent temperature rise inside the battery cell during fast charging, so that the fast charging performance can be maintained in long-term fast charging cycles, thereby improving the fast charging cycle life of the battery cell.
[0038] In any embodiment, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate and a modified material thereof.
[0039] In any embodiment, the porosity of the isolation membrane is 25%-55%, and can be optionally 28%-42%.
[0040] The isolation membrane with a porosity within the above range is conducive to improving the liquid phase transmission rate of lithium ions and reducing the liquid phase transmission resistance of lithium ions. Therefore, in order to achieve the same lithium ion liquid phase transmission rate, the content of chain carboxylic acid ester solvent required to be added is reduced, so that the battery monomer can further take into account the fast charging performance and cycle stability.
[0041] In any embodiment, the porosity of the isolation membrane is 28%-42%.
[0042] The porosity of the isolation membrane within the above range is conducive to further improving the liquid phase transmission rate of lithium ions, alleviating the uneven current density distribution on the electrode during fast charging and the inconsistent temperature rise inside the battery cell during fast charging, so that the fast charging performance can be maintained in long-term fast charging cycles, thereby improving the fast charging cycle life of the battery cell.
[0043] In any embodiment, the Gurley value G of the isolation membrane is 50s-620s, and can be optionally 300s-610s. The Gurley value refers to the time required for 100 mL of air to pass through 1 square inch of the isolation membrane under a pressure of 1.22 kPa when the isolation membrane is placed in an air permeability tester, and the unit is s.
[0044] The isolation membrane with a Gurley value within the above range is beneficial to improving the liquid phase transmission rate of lithium ions, thereby reducing the content of chain carboxylic acid ester solvents required to achieve the same lithium ion liquid phase transmission rate, so that the battery monomer can further take into account both fast charging performance and cycle stability.
[0045] In any embodiment, the separator includes a base film and a ceramic coating, and the ceramic coating is disposed only on the positive electrode side of the base film.
[0046] The main component of the ceramic coating is ceramic particles, which are flame retardant and have a high hardness value. They are not easily deformed by heat. Therefore, the ceramic coating is beneficial to improve the mechanical strength of the separator and reduce the probability of lithium dendrites that are easily formed during fast charging piercing the separator, causing short circuits in the battery and thermal runaway. Placing the ceramic coating only on the positive side of the base film can take into account both the fast charging performance and safety performance of the battery cell.
[0047] In any embodiment, the ceramic coating includes ceramic particles, and the ceramic particles include one or more of aluminum oxide, boehmite, silicon oxide, titanium oxide, magnesium oxide, calcium oxide, zinc oxide, zirconium oxide, and tin oxide, and can be selected from one or more of aluminum oxide and boehmite.
[0048] In any embodiment, the ceramic coating further includes a binder, and the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, water-soluble unsaturated resin SR-1B, water-based acrylic resin, polyacrylamide, and polyvinyl alcohol, and polyvinylidene fluoride can be selected.
[0049] In any embodiment, the battery cell comprises a wound cell, the negative current collector comprises a negative current collecting portion and a negative electrode tab disposed on at least one side of the negative current collecting portion, and at least one circle of the negative electrode sheet of the wound cell comprises at least two negative electrode tabs.
[0050] In any embodiment, the battery cell includes a wound cell, the positive current collector includes a positive current collecting portion and a positive electrode tab disposed on at least one side of the positive current collecting portion, and at least one circle of the positive electrode sheet of the wound cell includes at least two positive electrode tabs.
[0051] In the prior art, a positive electrode sheet or a negative electrode sheet in a wound battery cell is usually provided with a pole ear for each winding. The embodiment of the present application reduces the overcurrent at the pole ear by providing at least two pole ears on at least one winding of the pole sheet of the wound battery cell, reduces the temperature rise at the pole ear, reduces the degree of side reaction between the carboxylic acid ester solvent in the electrolyte and the lithium bis(fluorosulfonyl)imide and the negative electrode, and enables the battery cell to withstand a higher charging current, further improving the fast charging performance and safety performance of the battery cell. In addition, providing at least two pole ears on at least one winding of the pole sheet of the wound battery cell alleviates the uneven current density distribution on the pole sheet and the inconsistent temperature rise inside the battery cell during the fast charging process, so that the fast charging performance can be maintained in a long-term fast charging cycle, and the fast charging cycle life of the battery cell is improved.
[0052] In any embodiment, the wound battery cell includes a large surface area and a bending area, and the positive electrode lug is arranged in the large surface area of the wound battery cell. The number of layers of the positive electrode sheets in the wound battery cell is defined according to the rule that the number of layers of the positive electrode sheets in the large surface area increases successively along the winding direction from the inside to the outside, and the positive electrode sheets of the wound battery cell have at least two consecutive layers, each of which is provided with a positive electrode lug.
[0053] In the prior art, the pole tabs in the wound battery cell are generally arranged in the Nth layer, the N+2th layer, the N+4th layer, etc., and at most one pole tab is arranged in every two layers of the pole sheet in the wound battery cell. In the embodiment of the present application, the pole tabs are arranged in each of at least two consecutive layers in the pole sheet, that is, the pole tabs are continuously arranged in the Nth layer and the N+1th layer, so as to reduce the overcurrent at the pole tabs, reduce the temperature rise at the pole tabs, and reduce the degree of side reactions between the carboxylic acid ester solvent in the electrolyte and the lithium bis(fluorosulfonyl)imide and the negative electrode, while allowing the battery cell to withstand a higher charging current, further improving the fast charging performance and safety performance of the battery cell. In addition, at least two pole tabs are arranged on at least one circle of the pole sheet of the wound battery cell, so that the uneven current density distribution on the pole sheet and the inconsistent temperature rise inside the battery cell during the fast charging process are alleviated, so that the fast charging performance can be maintained in a long-term fast charging cycle, further improving the cycle life of the battery cell.
[0054] In any embodiment, the liquid injection coefficient of the battery cell is 2.5 g / Ah - 3.2 g / Ah, and can be optionally 2.8 g / Ah - 3.0 g / Ah.
[0055] Battery monomers with a liquid injection coefficient within the above range can not only keep the side reaction between the chain carboxylic acid ester solvent and the negative electrode active material at a low level, while taking into account the cycle life of the battery; they can also improve the wettability between the electrolyte and the electrode, reduce the battery interface resistance, reduce the battery impedance, and further improve the battery fast charging performance.
[0056] A second aspect of the present application provides a battery device, including the battery cell provided by the first aspect of the present application, and the battery device includes at least one of a battery module, a battery pack, and an energy storage battery.
[0057] The third aspect of the present application further provides an electrical device, which includes the battery cell provided in the first aspect of the present application or the battery device provided in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 is a schematic diagram of a battery cell according to an embodiment of the present application; Figure 2 is a schematic diagram of a battery module according to an embodiment of the present application; Figure 3 is a schematic diagram of a battery pack according to an embodiment of the present application; Figure 4 yes Figure 3 An exploded schematic diagram of a battery pack is shown; Figure 5 is an exploded schematic diagram of a battery cell according to an embodiment of the present application; Figure 6 is a schematic diagram of an electrical device using a battery cell as a power source according to an embodiment of the present application; Figure 7 It is a schematic diagram of a wound battery cell according to one embodiment of the present application.
[0059] Description of reference numerals: 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly; 6 wound battery cell; 61 large surface area; 62 bending area; 101 positive electrode sheet; 102 negative electrode sheet; 10112 positive electrode ear; 1023 negative electrode ear. DETAILED DESCRIPTION
[0060] Hereinafter, the battery cells, battery devices and power devices of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0061] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0062] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0063] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0064] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0065] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0066] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.
[0067] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.
[0068] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.
[0069] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.
[0070] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a box and battery cells, and the battery cells or battery modules are accommodated in the box. In some embodiments, the box may serve as part of the chassis structure of the vehicle. For example, part of the box may become at least a part of the floor of the vehicle, or part of the box may become at least a part of the crossbeam and longitudinal beam of the vehicle.
[0071] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.
[0072] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 2 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 2 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0073] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0074] In some embodiments, the battery modules and battery cells mentioned above may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0075] Figure 3 and Figure 4 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 3 and Figure 4 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.
[0076] The battery provided in the embodiment of the present application may include a lithium-ion battery.
[0077] A battery cell includes an electrode assembly and an electrolyte.
[0078] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0079] In some embodiments, Figure 5 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0080] The electrode assembly usually includes a positive electrode plate and a negative electrode plate. The negative electrode plate is an electrode that absorbs or lithiates lithium ions during charging and releases or delithiates lithium during discharging. The positive electrode plate is an electrode that releases or delithiates lithium ions during charging and absorbs or lithiates lithium during discharging.
[0081] In order to improve the kinetic performance of battery cells, it is usually necessary to add chain carboxylate solvents to the electrolyte to increase the ion transfer rate of the electrolyte. However, carboxylate solvents have high reactivity and are particularly prone to side reactions with negative electrode active materials at high temperatures, which deteriorates the cycle life of the battery. How to balance the fast charging performance and cycle life of the battery is a technical problem that urgently needs to be solved in this field.
[0082] Based on the above problems, an embodiment of the present application provides a battery cell, which includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator arranged between the positive electrode plate and the negative electrode plate; the electrolyte includes a solvent and an electrolyte salt, the electrolyte salt includes lithium bis(fluorosulfonyl)imide, and the mass proportion of the lithium bis(fluorosulfonyl)imide based on the total mass of the electrolyte is 1%-6%; the solvent includes a chain carboxylate solvent, and the mass proportion of the chain carboxylate solvent based on the total mass of the electrolyte is 5%-75%; the negative electrode plate includes a negative electrode collector and a negative electrode film layer arranged on at least one side of the negative electrode collector, the negative electrode film layer includes a negative electrode active material, and the degree of graphitization of the negative electrode active material is 90%-96%; the positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode collector includes an aluminum foil, and the thickness of the aluminum foil is 10μm-16μm.
[0083] Herein, the type and mass content of each component in the electrolyte can be obtained by detecting the electrolyte by any method known to those skilled in the art. As an example, the composition and content of the electrolyte can be characterized by one or more of gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), and gas chromatography-mass spectrometry (GC-MS). Exemplarily, referring to GB / T-9722-2006 / GB / T6041-2002, gas chromatography and mass spectrometry are used, and after the gas chromatography separates the components in the sample, the components are broken into ion fragments in the mass spectrum, and are separated according to the mass-to-charge ratio (m / z) to form a specific mass spectrum, and the qualitative analysis of the organic components in the electrolyte is obtained, and then the organic components in the electrolyte are separated in the chromatographic column and the detection signal spectra of each component are generated, and the retention time is used for component qualitative analysis, and the peak area is calibrated to achieve quantitative analysis, and the quantitative test analysis of the organic components in the electrolyte is obtained. Referring to JY / T-020, the anion species of the electrolyte salt in the electrolyte are detected by ion chromatography and quantitatively tested. Referring to JY / T 0578-2020, nuclear magnetic resonance spectroscopy (NMR) is used to obtain qualitative and quantitative analysis of the components in the electrolyte.
[0084] Herein, based on the total mass of the electrolyte, the mass content of the lithium bis(fluorosulfonyl)imide LiFSI can be calculated by dividing the mass of the lithium bis(fluorosulfonyl)imide LiFSI obtained by detection by the total mass of the electrolyte sample. The electrolyte referred to herein can be either a fresh electrolyte or an electrolyte obtained by disassembling a battery cell. The electrolyte obtained by disassembling a battery cell can be either a free electrolyte in the battery casing or an electrolyte obtained by centrifugation from a pole piece.
[0085] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide LiFSI may be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% or any range therebetween.
[0086] In the present application, the linear carboxylate solvent refers to a linear organic solvent containing a carboxylate group.
[0087] Herein, based on the total mass of the electrolyte, the mass content of the chain carboxylate solvent can be calculated by dividing the mass of the chain carboxylate solvent obtained by detection by the total mass of the electrolyte sample.
[0088] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the linear carboxylate solvent can be selected to be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or any numerical range therebetween.
[0089] In some embodiments, the negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As examples of metal foils, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil may be used. As examples of three-dimensional porous current collectors, copper mesh, nickel mesh, foam copper, foam nickel, and foam aluminum may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0090] In some embodiments, the negative electrode film layer includes a negative electrode active material, which may be a graphite negative electrode active material.
[0091] In this article, the term "degree of graphitization" macroscopically characterizes the proportion of the material that reaches a complete graphite crystal structure; microscopically, it refers to the degree to which the carbon structure in different transition states is close to the ideal graphite crystal.
[0092] The graphitization degree of graphite negative electrode active materials reflects the completeness of the graphite crystal structure in the material, that is, the regularity of the arrangement of carbon atoms in the graphite structure in the material. A high graphitization degree of the material indicates that the graphite interlayer spacing is small, the smaller the lattice rotation, the less scattered stacking of the layers, the more orderly the arrangement, and the high gram capacity of the material, which is conducive to obtaining a battery cell with high energy density. A low graphitization degree of the material indicates that the graphite has a large degree of disorder and a large interlayer spacing, which is conducive to the rapid deintercalation of active ions, the expansion of the material is small when lithium is inserted, and it has the effect of shallow charge and discharge, which is conducive to the improvement of battery kinetic performance.
[0093] In the present application, the graphitization degree of the graphite negative electrode active material can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JISK0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material crystal structure. 002 Then according to the formula g=(0.344-d 002 ) / (0.344-0.3354)×100% to calculate the degree of graphitization. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).
[0094] In some embodiments, the degree of graphitization of the negative electrode active material may be 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, or any range therebetween.
[0095] The addition of chain carboxylic acid ester solvents to the electrolyte is not only beneficial to improving the lithium ion conductivity of the electrolyte, but also can reduce the viscosity of the electrolyte, improve the flow of the electrolyte in the width direction of the electrode, increase the transmission rate of lithium ions at the solid-liquid interface of the battery monomer, reduce the internal resistance of the battery monomer, and improve the fast charging performance of the battery. However, chain carboxylic acid ester solvents have high reactivity, especially easy to react with negative electrode active materials at high temperatures, resulting in battery gas production and deteriorating the high temperature cycle life of the battery. Lithium bis(fluorosulfonyl)imide LiFSI is prone to dissociation in the electrolyte solvent, which is beneficial to further improve the transmission rate of lithium ions in the battery. Therefore, adding a certain amount of lithium bis(fluorosulfonyl)imide LiFSI to the chain carboxylic acid ester solvent can reduce the amount of chain carboxylic acid ester solvent in the electrolyte while maintaining the fast charging performance of the battery, and reduce the degree of side reactions of chain carboxylic acid ester solvents. At the same time, LiFSI has better thermal stability than other electrolyte salts (such as lithium hexafluorophosphate), which can reduce the probability of electrolyte salt decomposition at high temperature to produce hydrogen fluoride, so that the high temperature cycle life of the battery can be improved. However, lithium bis(fluorosulfonyl)imide LiFSI is prone to violent side reactions with deeply lithium-intercalated negative electrode active materials (such as LiC6), which poses a safety hazard to the battery. The lithium-intercalation depth of the negative electrode active material is correlated with its graphitization degree. The lithium-intercalation depth of the negative electrode active material increases with the increase of the graphitization degree. Reducing the graphitization degree of the negative electrode active material can reduce the probability of generating deeply lithium-intercalated negative electrode active materials (such as LiC6) and increase the transfer rate of lithium ions at the solid-liquid interface, so that the solid-liquid transfer rate of lithium ions can match the high liquid phase transfer rate of chain carboxylic acid ester solvents, which is beneficial to improve the fast charging performance of the battery. However, the reduction of the graphitization degree of the negative electrode active material will also lead to an increase in the degree of side reactions between the chain carboxylic acid ester solvent and the negative electrode active material, deteriorating the high-temperature cycle stability of the battery.
[0096] During the research process, the applicant found that the negative electrode active material with a graphitization degree within the above range is combined with an electrolyte containing a chain carboxylic acid ester solvent and lithium bis(fluorosulfonyl)imide LiFSI, which can not only reduce the probability of side reactions between the electrolyte and the defect sites of the negative electrode active material at high temperature, but also reduce the degree of side reactions between lithium bis(fluorosulfonyl)imide LiFSI and the negative electrode active material with deep lithium insertion. It can also form a match between the solid-liquid transfer rate of lithium ions and the liquid phase transfer rate through a certain degree of disorder of the negative electrode active material and the chain carboxylic acid ester solvent, promote the rapid insertion and removal of lithium ions in the negative electrode active material, and achieve a balance between the fast charging performance, safety performance and high-temperature cycle life of the battery cell.
[0097] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide is 1.5%-5%.
[0098] Based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide within the above range is beneficial to further improve the safety of the battery while maintaining good fast charging performance and high-temperature cycle life of the battery.
[0099] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the linear carboxylate solvent is 10%-65%.
[0100] Based on the total mass of the electrolyte, a mass proportion of the chain carboxylic acid ester solvent within the above range is beneficial for taking into account both the fast charging performance and high temperature cycle life of the battery monomer.
[0101] In some embodiments, the graphitization degree of the negative electrode active material is 92%-95%.
[0102] In some embodiments, based on the total mass of the electrolyte salt in the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is 10%-50%.
[0103] In some embodiments, based on the total mass of the electrolyte salt in the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide may be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any range therebetween.
[0104] When the mass proportion of lithium bis(fluorosulfonyl)imide LiFSI in the electrolyte salt of the electrolyte is within the above range, it can not only reduce the amount of chain carboxylic acid ester solvents used to a certain extent, but also reduce the production of hydrogen fluoride in the battery during high-temperature cycles, and also alleviate the degree of reaction between LiFSI and deeply lithium-embedded negative electrode active materials, which together improve the high-temperature cycle performance and safety performance of the battery monomer.
[0105] In some embodiments, the linear carboxylate solvent includes one or more of ethyl acetate, methyl acetate, methyl formate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, propyl butyrate, butyl butyrate, isopropyl acetate, and isoamyl acetate.
[0106] The above-mentioned chain carboxylate solvent molecules have higher lithium ion conductivity. Compared with other chain carboxylate solvents, only a small amount of addition is needed to achieve higher lithium ion conductivity. While improving the fast charging performance of battery cells, it can effectively control the degree of side reactions between the electrolyte and the negative electrode active material, allowing the battery cells to further improve the cycle stability while maintaining good fast charging performance.
[0107] In some embodiments, the linear carboxylate solvent includes one or more of ethyl acetate and methyl acetate.
[0108] Compared with other carboxylic acid ester solvents, ethyl acetate and methyl acetate have better kinetic activity and relatively low gas production levels, which are beneficial to further improve the lithium ion transmission rate and reduce the level of side reactions between the electrolyte and the negative electrode at high temperatures, while taking into account the fast charging performance and high-temperature cycle stability of the battery cells.
[0109] In some embodiments, based on the total mass of the solvent, the total mass of ethyl acetate and methyl acetate accounts for 5%-80%, and can be optionally 10%-70%.
[0110] In some embodiments, based on the total mass of the solvent, the total mass proportion of ethyl acetate and methyl acetate can be selected to be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or any numerical range therebetween.
[0111] In some embodiments, the linear carboxylic acid ester solvent includes methyl acetate.
[0112] In some embodiments, based on the total mass of the solvent, the mass content of methyl acetate is 5%-80%, optionally 5%-50%, and further optionally 10%-40%.
[0113] In some embodiments, the mass content of methyl acetate can be selected as 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or any numerical range therebetween, based on the total mass of the solvent.
[0114] In some embodiments, the solvent further includes a carbonate solvent, and the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0115] In some embodiments, the solvent includes ethylene carbonate, and the mass content of ethylene carbonate is 15%-35% based on the total mass of the solvent.
[0116] Ethylene carbonate has a high dielectric constant, which is beneficial to improve the solubility of lithium salts in the electrolyte, increase the lithium ion concentration in the electrolyte, improve the conductivity of the electrolyte, and improve the fast charging performance of the battery. At the same time, ethylene carbonate has good film-forming properties, which is beneficial to improve the quality of the SEI film on the surface of the negative electrode, reduce the degree of side reactions between carboxylic acid esters and the negative electrode, and improve the cycle life of the battery.
[0117] In some embodiments, based on the total mass of the solvent, the mass content of ethylene carbonate may be 15%, 20%, 25%, 30%, 35% or any range therebetween.
[0118] In some embodiments, the solvent includes dimethyl carbonate, and the mass content of dimethyl carbonate is 5%-50% based on the total mass of the solvent.
[0119] In some embodiments, based on the total mass of the solvent, the mass content of dimethyl carbonate can be selected as 5%, 10%, 20%, 30%, 40%, 50% or any numerical range therebetween.
[0120] Dimethyl carbonate has good electrical conductivity and gas production performance. Adding dimethyl carbonate to the electrolyte can appropriately reduce the content of carboxylic acid ester in the electrolyte, thereby reducing the degree of side reaction between carboxylic acid ester and the negative electrode, and improving the cycle life of the battery while maintaining the fast charging performance of the battery.
[0121] In some embodiments, the negative electrode current collector includes copper foil, and the thickness of the copper foil is 4 μm-6 μm, and optionally 4 μm-5 μm.
[0122] In some embodiments, the thickness of the copper foil may be 4 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6 μm or any range therebetween.
[0123] When the thickness of the copper foil is within the above range, it can reduce the internal resistance of the battery and the heat generated by the battery cells during fast charging through a certain current collector thickness, so that the battery cells can withstand higher charging currents and improve the battery fast charging performance and safety performance; it can also increase the energy density of the battery by thinning the current collector, thereby taking into account both the fast charging performance and energy density of the battery cells.
[0124] In some embodiments, the single-side density of the negative electrode film layer is 0.08 g / 1540.25 mm 2 -0.20g / 1540.25mm 2 , optional 0.10 g / 1540.25mm 2 -0.16 g / 1540.25 mm 2 .
[0125] In the present application, the surface density of the film layer has a well-known meaning in the art and can be tested by methods known in the art. For example, take a pole piece that is coated on one side and cold pressed (if it is a pole piece coated on both sides, the film layer on one side can be wiped off), punch it into small discs with an area of S1, weigh it, and record it as M1. Then wipe off the film layer of the pole piece after the above weighing, weigh the weight of the current collector, and record it as M0. The single-side density of the film layer = (M1-M0) / S1. In order to ensure the accuracy of the test results, multiple groups (for example, 10 groups) of samples to be tested can be tested, and the average value can be calculated as the test result.
[0126] In some embodiments, the single-side density of the negative electrode film layer can be selected to be 0.08 g / 1540.25 mm 2 , 0.09g / 1540.25mm 2 , 0.10g / 1540.25mm 2 , 0.11g / 1540.25mm 2 , 0.12g / 1540.25mm 2 , 0.13g / 1540.25mm 2 , 0.14g / 1540.25mm 2 , 0.15g / 1540.25mm 2 , 0.16g / 1540.25mm 2 , 0.17g / 1540.25mm 2 , 0.18g / 1540.25mm 2 , 0.19g / 1540.25mm 2 , 0.20g / 1540.25mm 2 Or any range of values in between.
[0127] It can be understood that the single-side density of the negative electrode film layer is tested on the negative electrode sheet, and the single-side density of the positive electrode film layer is tested on the positive electrode sheet.
[0128] A battery cell with a single side density of the negative electrode film layer within the above range can reduce the transmission distance of lithium ions in the negative electrode film layer, match with an electrolyte with high conductivity, reduce the concentration polarization generated by the battery cell during fast charging, and enable the battery cell to withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0129] In some embodiments, the compaction density of the negative electrode sheet is 1.2 g / cm 3 -1.9 g / cm 3 , optional 1.2 g / cm 3 -1.65g / cm 3 .
[0130] In this application, the compaction density of the negative electrode plate has a well-known meaning in the art and can be tested by methods known in the art. Remove the negative electrode plate from the lithium-ion battery, take a certain area of the plate, and measure the mass and thickness of the plate and the current collector after removing the film layer. Calculate the compaction density of the plate according to the following formula. Compaction density of the plate = (plate mass - current collector mass) / [(plate thickness - current collector thickness) × plate area].
[0131] In some embodiments, the compaction density of the negative electrode sheet can be selected to be 1.2 g / cm 3 , 1.3 g / cm 3 , 1.4 g / cm 3 , 1.5 g / cm 3 , 1.6 g / cm 3 , 1.65 g / cm 3 , 1.7 g / cm 3 , 1.8 g / cm 3 , 1.9 g / cm 3 Or any range of values in between.
[0132] The negative electrode sheet with a compaction density within the above range has a suitable porosity, can match the electrolyte with high conductivity, increase the diffusion rate of lithium ions in the negative electrode, reduce the concentration polarization generated during fast charging, and enable the battery cell to withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0133] In some embodiments, the average thickness of a single side of the negative electrode film layer is 30 μm-150 μm, and optionally 30 μm-80 μm.
[0134] In some embodiments, the average thickness of a single side of the negative electrode film layer may be selected to be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm or any range of values therebetween.
[0135] A battery cell with an average single-side thickness of the negative electrode film layer within the above range can reduce the transmission distance of lithium ions in the negative electrode film layer, match with an electrolyte with high conductivity, reduce the concentration polarization generated by the battery cell during fast charging, and enable the battery cell to withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0136] In some embodiments, the porosity of the negative electrode sheet is 20%-60%, and can be optionally 25%-40%.
[0137] In the present application, the porosity of the negative electrode plate can be tested by methods known in the art. For example, the test is based on the national standard GB / T24586-2009, the plate is immersed in ethyl methyl carbonate (EMC) for cleaning; the test instrument true density meter (American Micrometer AccuPycII1340) is used to measure based on the gas replacement method. Among them, the percentage of the pore volume in the plate to the total volume of the plate is the plate porosity, and the calculation formula is: Porosity = (V-V0) / V×100%, where V0 is the true volume of the plate, and V is the apparent volume of the plate.
[0138] In some embodiments, the porosity of the negative electrode sheet may be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any range therebetween.
[0139] The negative electrode plate with a porosity within the above range can be matched with an electrolyte with high conductivity, thereby increasing the diffusion rate of lithium ions in the negative electrode and reducing the concentration polarization generated by the battery cell during fast charging, so that the battery cell can withstand a larger charging current, which is beneficial to improving the fast charging performance and safety performance of the battery cell.
[0140] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, the positive electrode current collector includes aluminum foil, and the thickness of the aluminum foil is 10 μm-16 μm, and can be 11 μm-14 μm.
[0141] The material of the positive electrode current collector is not particularly limited, as long as it does not cause chemical changes in the battery cell and has conductivity, the current collector includes a metal foil with a pure metal content of more than 95%, for example: at least one of copper foil, aluminum foil, stainless steel foil, titanium foil, and nickel foil, and also includes at least two main gold alloy foils, for example, can be made of alloy foils of at least two main elements of copper, aluminum, nickel, titanium, and iron, and can also include copper, aluminum-cadmium alloy, iron or stainless steel treated with carbon, nickel, titanium, silver, copper, etc. In addition, the binding force with the negative electrode active material can be enhanced by forming fine concave and convex on the surface, and can be used in various forms such as film, sheet, foil, net, porous body, foam, non-woven fabric, etc.
[0142] In some embodiments, the thickness of the aluminum foil may be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, or any range therebetween.
[0143] When the thickness of the aluminum foil is within the above range, it can reduce the internal resistance of the battery and the heat generation of the battery cells under high-rate charge and discharge through a certain current collector thickness, thereby improving the fast charging performance and safety performance of the battery; it can also increase the energy density of the battery by thinning the current collector, thereby taking into account both the fast charging performance and energy density of the battery cells.
[0144] In some embodiments, the thickness of the aluminum foil is 11 μm to 14 μm.
[0145] The thickness of the aluminum foil within the above range can further improve the current collector's current carrying capacity, alleviate the uneven current density distribution on the electrode and the inconsistent temperature rise inside the battery cell during fast charging, so that the fast charging performance can be maintained in long-term fast charging cycles, thereby improving the fast charging cycle life of the battery cell.
[0146] In some embodiments, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate and a modified material thereof.
[0147] In some embodiments, the modified material of lithium iron phosphate includes one or more of a lithium iron phosphate coating material and a lithium iron phosphate doping material.
[0148] In some embodiments, the porosity of the isolation membrane is 25%-55%, and can be optionally 28%-42%.
[0149] In the present application, the porosity of the isolation membrane can be measured by methods known in the art. As an example, the porosity is measured by the gas displacement method in accordance with GB / T24586. Porosity ε = (V1-V2) / V1*100%, where V1 is the apparent volume of the sample and V2 is the real volume of the sample.
[0150] In some embodiments, the porosity of the isolation membrane may be selected to be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 50%, 55% or any range therebetween.
[0151] The isolation membrane with a porosity within the above range is conducive to improving the liquid phase transmission rate of lithium ions and reducing the liquid phase transmission resistance of lithium ions. Therefore, in order to achieve the same lithium ion liquid phase transmission rate, the content of chain carboxylic acid ester solvent required to be added is reduced, so that the battery monomer can further take into account the fast charging performance and cycle stability.
[0152] In some embodiments, the porosity of the isolation membrane is 30%-42%.
[0153] The porosity of the isolation membrane within the above range is conducive to further improving the liquid phase transmission rate of lithium ions, alleviating the uneven current density distribution on the electrode during fast charging and the inconsistent temperature rise inside the battery cell during fast charging, so that the fast charging performance can be maintained in long-term fast charging cycles, thereby improving the fast charging cycle life of the battery cell.
[0154] In some embodiments, the Gurley value G of the isolation film is 50s-620s, and can be optionally 300s-610s.
[0155] In this application, the term "Gurley value" is used to characterize the air permeability of an isolation membrane, which refers to the time required for 100 mL of air to pass through 1 square inch of the isolation membrane under a pressure of 1.22 kPa, with the unit being s.
[0156] In the present application, the Gurley value of the isolation membrane can be tested by any known means. As an example, the isolation membrane is placed in an air permeability tester, and the time required for 100 mL of air to pass through 1 square inch of the isolation membrane under a pressure of 1.22 kPa is the Gurley value. The average value of the test results of multiple (for example, 3) parallel samples can be taken as the Gurley value of the isolation membrane.
[0157] In some embodiments, the Gurley value G of the isolation film can be selected as 50s, 100s, 150s, 200s, 250s, 260s, 270s, 280s, 290s, 300s, 310s, 320s, 330s, 340s, 350s, 360s, 370s, 380s, 390s, 400s, 410s, 420s, 430s, 440s, 450s, 460s, 470s, 480s, 490s, 500s, 510s, 520s, 530s, 540s, 550s, 560s, 570s, 580s, 590s, 600s, 610s, 620s or any numerical range therebetween.
[0158] The isolation membrane with a Gurley value within the above range is beneficial to improving the liquid phase transmission rate of lithium ions, thereby reducing the content of chain carboxylic acid ester solvents required to achieve the same lithium ion liquid phase transmission rate, so that the battery monomer can further take into account both fast charging performance and cycle stability.
[0159] In some embodiments, the material of the isolation membrane may include, but is not limited to, one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP), and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0160] In some embodiments, the separator includes a base film and a ceramic coating, and the ceramic coating is disposed only on the positive electrode side of the base film.
[0161] The main component of the ceramic coating is ceramic particles, which are flame retardant and have a high hardness value. They are not easily deformed by heat. Therefore, the ceramic coating is beneficial to improve the mechanical strength of the separator and reduce the probability of lithium dendrites that are easily formed during fast charging piercing the separator, causing short circuits in the battery and thermal runaway. Placing the ceramic coating only on the positive side of the base film can take into account both the fast charging performance and safety performance of the battery cell.
[0162] In some embodiments, the ceramic coating includes ceramic particles, and the ceramic particles include one or more of aluminum oxide, boehmite, silicon oxide, titanium oxide, magnesium oxide, calcium oxide, zinc oxide, zirconium oxide, and tin oxide, and can be one or more of aluminum oxide and boehmite.
[0163] In some embodiments, the ceramic coating further includes a binder, and the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, water-soluble unsaturated resin SR-1B, water-based acrylic resin, polyacrylamide, and polyvinyl alcohol, and polyvinylidene fluoride can be selected.
[0164] In some embodiments, Figure 7 As shown, the battery cell includes a wound cell 6 , the positive current collector includes a positive current collecting portion and a positive electrode tab 10112 arranged on at least one side of the positive current collecting portion, and at least one circle of the positive electrode sheet 101 of the wound cell 6 includes at least two positive electrode tabs 10112 .
[0165] In some embodiments, please continue to refer to Figure 7 The battery cell includes a wound battery cell 6, the negative electrode current collector includes a negative electrode current collecting portion and a negative electrode tab 1023 arranged on at least one side of the negative electrode current collecting portion, and at least one circle of the negative electrode sheet 102 of the wound battery cell 6 includes at least two negative electrode tabs 1023.
[0166] The tabs are connected to the battery housing or external module structure, and the current must flow through the tabs to connect to the outside of the battery.
[0167] In some embodiments, the tab extending in the width direction of the current collector means that the tab is located at the end of the battery cell in the height direction.
[0168] In some embodiments, the wound battery cell 6 is as follows Figure 7 As shown, it is a square wound battery cell.
[0169] In some embodiments, the wound battery cell 6 is a cylindrical wound battery cell. Figure 7Whether in a square wound cell or a cylindrical wound cell, one circle of the positive electrode sheet refers to the winding direction from any point A of the positive electrode sheet, which is free from inside to outside, that is, winding Figure 7 After winding around the winding needle once in the clockwise direction, it is wound to the point B which is closest to point A in the next circle.
[0170] In some embodiments, at least one turn of the positive electrode sheet 101 of the wound battery cell 6 includes at least three, four, five or more tabs.
[0171] In some embodiments, at least two, three, four or more consecutive turns of the positive electrode sheet 101 of the wound battery cell 6 each include at least two tabs.
[0172] In the prior art, a positive electrode sheet or a negative electrode sheet in a wound battery cell is usually provided with a pole ear for each winding. The embodiment of the present application reduces the overcurrent at the pole ear by providing at least two pole ears on at least one winding of the pole sheet of the wound battery cell, reduces the temperature rise at the pole ear, reduces the degree of side reaction between the carboxylic acid ester solvent in the electrolyte and the lithium bis(fluorosulfonyl)imide and the negative electrode, and enables the battery cell to withstand a higher charging current, further improving the fast charging performance and safety performance of the battery cell. In addition, providing at least two pole ears on at least one winding of the pole sheet of the wound battery cell alleviates the uneven current density distribution on the pole sheet and the inconsistent temperature rise inside the battery cell during the fast charging process, so that the fast charging performance can be maintained in a long-term fast charging cycle, and the fast charging cycle life of the battery cell is improved.
[0173] In some embodiments, the wound battery cell 6 is as follows Figure 7 As shown, the wound cell 6 includes a large surface area 61 and a bending area 62, and the positive electrode tab 10112 is arranged on the large surface area 61 of the wound cell 6, and is wound along the winding direction from inside to outside (such as Figure 7 The number of layers of the positive electrode sheets in the wound battery cell is defined by the rule that the number of positive electrode sheets in the large surface area increases successively (clockwise direction in the figure). The positive electrode sheets of the wound battery cell 6 have at least two consecutive layers, each of which is provided with a positive electrode ear.
[0174] As an example, a layer of the large surface area of the positive electrode sheet 101 is taken as the Nth layer of the positive electrode sheet, and the positive electrode sheet is wound in a direction from inside to outside (eg Figure 7 In the clockwise direction in the figure), the positive electrode sheet 101 passes through the bending area 62 and is wound to the large surface area on the opposite side of the Nth layer. The positive electrode sheet of this layer is recorded as the N+1 layer. The winding direction continues from the inside to the outside, and the positive electrode sheet passes through the bending area on the other side and is wound to the N+2 layer on the same side as the Nth layer. And so on, the number of layers of the positive electrode sheet 101 is defined.
[0175] In some embodiments, the positive electrode sheet of the wound battery cell has at least three, four, five, six or more consecutive layers, each of which is provided with a positive electrode tab.
[0176] In the prior art, the pole tabs in the wound battery cell are generally arranged in the Nth layer, the N+2th layer, the N+4th layer, etc., and at most one pole tab is arranged in every two layers of the pole sheet in the wound battery cell. In the embodiment of the present application, the pole tabs are arranged in each of at least two consecutive layers in the pole sheet, that is, the pole tabs are continuously arranged in the Nth layer and the N+1th layer, so as to reduce the overcurrent at the pole tabs, reduce the temperature rise at the pole tabs, and reduce the degree of side reactions between the carboxylic acid ester solvent in the electrolyte and the lithium bis(fluorosulfonyl)imide and the negative electrode, while allowing the battery cell to withstand a higher charging current, further improving the fast charging performance and safety performance of the battery cell. In addition, at least two pole tabs are arranged on at least one circle of the pole sheet of the wound battery cell, so that the uneven current density distribution on the pole sheet and the inconsistent temperature rise inside the battery cell during the fast charging process are alleviated, so that the fast charging performance can be maintained in a long-term fast charging cycle, further improving the cycle life of the battery cell.
[0177] It can be understood that the tabs in the negative electrode plate can be configured in the same manner as the positive electrode plate.
[0178] In some embodiments, the negative electrode sheet of the wound battery cell has at least two, three, four, five, six or more consecutive layers, each of which is provided with a negative electrode tab.
[0179] In some embodiments, the liquid injection coefficient of the battery cell is 2.5 g / Ah - 3.2 g / Ah, and can be optionally 2.8 g / Ah - 3.0 g / Ah.
[0180] The injection coefficient of a battery cell refers to the ratio of the mass of the electrolyte inside the battery cell to the battery capacity. The injection coefficient of a battery cell can be obtained by testing in any known manner in the art. For example, the battery cell is weighed and the mass is recorded as M0. The battery cell is disassembled and the free electrolyte is poured out; the internal electrode assembly is taken out and the positive electrode sheet, negative electrode sheet, separator and mechanical parts are separated, and the positive electrode sheet, negative electrode sheet, separator and mechanical parts are soaked and cleaned with dimethyl carbonate (DMC) solvent for 24h~48h, and the soaking time is repeated for more than 3 times. The above-mentioned positive electrode sheet, negative electrode sheet, separator and mechanical parts are placed in a 100°C oven for more than 24h until completely dried. The above-mentioned dried positive electrode sheet, negative electrode sheet, separator and mechanical parts are weighed and the mass is recorded as M1. The mass of the electrolyte in the battery cell is thus obtained as (M0-M1). The injection coefficient is calculated by (M0-M1) / rated capacity of the battery cell. The rated capacity of a battery cell is the nominal capacity of the battery, or it is charged to 3.65V at a 0.33C charge rate, then charged to 0.05C at a 3.65V constant voltage, left to rest for 10 minutes, and then discharged to 2.0V at a 0.33C discharge rate, with the discharge capacity of the battery cell as the rated capacity. It is understandable that in order to improve the accuracy of the injection coefficient test, it is better to use the battery that has just been shipped for testing.
[0181] In some embodiments, the liquid filling coefficient of the battery cell may be 2.5 g / Ah, 2.6 g / Ah, 2.7 g / Ah, 2.8 g / Ah, 2.9 g / Ah, 3 g / Ah, 3.1 g / Ah, 3.2 g / Ah or any range therebetween.
[0182] Battery monomers with a liquid injection coefficient within the above range can not only keep the side reaction between the chain carboxylic acid ester solvent and the negative electrode active material at a low level, while taking into account the cycle life of the battery; they can also improve the wettability between the electrolyte and the electrode, reduce the battery interface resistance, reduce the battery impedance, and further improve the battery fast charging performance.
[0183] In some embodiments, the negative electrode film layer may also optionally include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0184] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the negative electrode binder may include, but is not limited to, one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0185] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include but are not limited to thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.
[0186] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, negative electrode conductive agent, negative electrode binder, other optional additives, etc. in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0187] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.
[0188] In some embodiments, the positive electrode current collector includes a positive electrode active material. The positive electrode active material may be a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523)、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0189] In some embodiments, the positive electrode film layer may also optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include but is not limited to one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0190] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) or more.
[0191] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, positive electrode conductive agent, positive electrode binder and any other components in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0192] In some embodiments, the electrolyte salt may also include, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP).
[0193] In some embodiments, the solvent further includes, but is not limited to, one or more of an ester solvent, a sulfone solvent, and an ether solvent. As an example, the solvent may include, but is not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0194] In some embodiments, the electrolyte may optionally include other additives.
[0195] A second aspect of the present application provides a battery device, including the battery cell provided by the first aspect of the present application, and the battery device includes at least one of a battery module, a battery pack, and an energy storage battery.
[0196] In addition, the third aspect of the present application further provides an electric device, which includes the battery cell provided in the first aspect of the present application or the battery device provided in the second aspect of the present application. The battery cell, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0197] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0198] Figure 6The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.
[0199] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0200] Example Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0201] 1. Preparation method Example 1
[0202] (1) Preparation of negative electrode sheet The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose, negative electrode binder styrene butadiene rubber (SBR), and negative electrode conductive agent Super P are mixed in a mass ratio of 96.9:1.1:1.5:0.5, and deionized water is added as a solvent. The mixture is stirred evenly under the action of a vacuum mixer to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the double-sided surface of the negative electrode current collector copper foil once or multiple times, and the thickness of the copper foil is 4.5μm. After drying, the negative electrode film layer is obtained, cold pressed, and cut to obtain the negative electrode sheet. The graphitization degree of the negative electrode active material is 93%, the thickness of the negative electrode film layer on one side of the negative electrode current collector is 53μm, and the single-side density of the negative electrode film layer is 0.131g / 1540.25mm 2 The compaction density of the negative electrode is 1.6g / cm 3 The porosity of the negative electrode sheet is 30%.
[0203] (2) Preparation of positive electrode The lithium iron phosphate positive electrode material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were added to the solvent N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5, and the positive electrode slurry (solid content of 67%) was obtained after being fully stirred and mixed. Then, the positive electrode slurry was evenly coated on the double-side surface of the positive electrode current collector aluminum foil, wherein the thickness of the aluminum foil was 13 μm, and the single-side coating weight was about 350 mg / 1540.25 mm 2 After drying, the positive electrode film layer is obtained, which is then cold pressed and cut to obtain the positive electrode sheet.
[0204] (3) Preparation of electrolyte In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and methyl acetate were evenly mixed in a mass ratio of 3:2:5, and then additives were added. The additives included vinylene carbonate VC, fluoroethylene carbonate FEC, lithium difluorooxalatoborate LiDFOB and 1,3-propyl sultone PS. Based on the total mass of the electrolyte, the mass proportion of VC was 2%, the mass proportion of FEC was 1%, the mass proportion of LiDFOB was 0.5%, and the mass proportion of PS was 1%.
[0205] After mixing evenly, lithium hexafluorophosphate (LiPF6) and LiFSI are added to dissolve them in the organic solvent. Based on the total mass of the electrolyte, the mass proportion of LiPF6 is 9%, and the mass proportion of LiFSI is 5%. Stir evenly to obtain an electrolyte.
[0206] (4) Preparation of isolation membrane A conventional commercially available polyethylene film is used as the isolation membrane. The surface of the isolation membrane facing the positive electrode is provided with a ceramic coating, which contains Al2O3 and PVDF adhesive. The porosity of the isolation membrane is 36%, and the Gurley value of the isolation membrane is 601s.
[0207] (5) Preparation of battery cells The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a battery cell, so that each layer of the positive electrode sheet and the negative electrode sheet in the wound battery cell is provided with a pole ear. The battery cell is placed in a battery housing, and after drying, the electrolyte is injected, and then a lithium-ion battery is obtained through processes such as formation and static.
[0208] The capacity of the prepared lithium-ion battery and the quality of the electrolyte were tested, and the battery filling coefficient was calculated to be 3.0 g / Ah.
[0209] The preparation methods of Examples 2-10 are substantially the same as those of Example 1, except that the corresponding parameters of the battery cells are adjusted, as shown in Table 1.
[0210] In Example 2, based on the total mass of the electrolyte, the mass content of lithium bis(fluorosulfonyl)imide is 1.5%, and the mass content of LiPF6 is 12.5%.
[0211] In Example 3, based on the total mass of the electrolyte, the mass content of lithium bis(fluorosulfonyl)imide is 5.8%, and the mass content of LiPF6 is 8.2%.
[0212] The solvent of the electrolyte in Example 4 is ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl acetate, and the mass ratio of the solvents is 3:2:5.
[0213] The solvent of the electrolyte in Example 5 is ethylene carbonate (EC), ethyl methyl carbonate (EMC) and methyl acetate in a mass ratio of 30:62:8, so that the mass content of carboxylic acid ester is 6.52% based on the total mass of the electrolyte.
[0214] The solvent of the electrolyte in Example 6 is ethylene carbonate (EC) and methyl acetate in a mass ratio of 2:8, so that the mass content of carboxylic acid ester is 65.2% based on the total mass of the electrolyte.
[0215] The graphitization degree of the negative electrode active material in Example 7 is 91%.
[0216] In Example 8, the number of pole tabs is adjusted so that one pole tab is provided for every two layers of the positive electrode sheets and the negative electrode sheets in the wound battery cell.
[0217] In Example 9, the porosity of the isolation membrane was adjusted, and the porosity of the isolation membrane was 28%.
[0218] In Example 10, the thickness of the aluminum foil in the positive electrode current collector was adjusted, and the thickness of the aluminum foil was 10 μm.
[0219] The preparation method of Comparative Example 1 is basically the same as that of Example 8, except that the electrolyte salt content in the electrolyte is adjusted so that the mass content of LIFSI is 8% and the mass content of LiPF6 is 6% based on the total mass of the electrolyte.
[0220] The preparation method of Comparative Example 2 is substantially the same as that of Example 8, except that the degree of graphitization of the negative electrode active material is 88%.
[0221] The preparation method of Comparative Example 3 is substantially the same as that of Example 8, except that the degree of graphitization of the negative electrode active material is 98%.
[0222] 2. Performance Test 1) Battery fast charging performance The batteries of the above embodiments and comparative examples were charged and discharged for the first time at a current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour), specifically comprising: at 35°C, the battery was charged at a constant current rate of 1C to a voltage of 3.65V, then charged at a constant voltage to a current ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a voltage of 2.5V, and its actual capacity was recorded as C0. Then the battery is charged with constant current of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, 3.5C0, 4C0, 4.5C0, 5C0 in sequence to the full battery charge cut-off voltage of 3.65V or 0V negative electrode cut-off potential (whichever is reached first). After each charge is completed, it is necessary to discharge with 1C0 to the full battery discharge cut-off voltage of 2.1V. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80% Charge, state of charge, when "SOC=0" means the battery is fully discharged, when "SOC=100%" means the battery is fully charged) the corresponding negative electrode potential, draw the charging rate-negative electrode potential curve under different SOC states, and obtain the charging rate corresponding to the negative electrode potential of 0V under different SOC states after linear fitting. The charging rate is the charging window under the SOC state, which are recorded as C(10%SOC), C(20%SOC), C(30%SOC), C(40%SOC), C(50%SOC), C(60%SOC), C(70%SOC), C(80%SOC), and the maximum charging rate under the corresponding charge state, that is, the fast charging window, is obtained. The charging time from 10% to 80% is 6 / C(20%SOC) + 6 / C(30%SOC) +6 / C(40%SOC) +6 / C(50%SOC) +6 / C(60%SOC) +6 / C(70%SOC) +6 / C(80%SOC), in minutes.
[0223] 2) Battery fast charging cycle number At 25°C, the obtained fast charge window distribution was used for charging, using a rate of C(10% SOC) to charge to 10% SOC, a rate of C(20% SOC) to charge to 20% SOC, a rate of C(30% SOC) to charge to 30% SOC, a rate of C(40% SOC) to charge to 40% SOC, a rate of C(50% SOC) to charge to 50% SOC, a rate of C(60% SOC) to charge to 60% SOC, a rate of C(70% SOC) to charge to 70% SOC, a rate of C(80% SOC) to charge to 80% SOC, 0.33C Charge to 100% SOC, let stand for 10 minutes, then charge to 2.1V with 0.33C DC, record the discharge capacity at this time as C1, monitor the temperature rise at the pole ear during this charging process, repeat the above process, record the discharge capacity of each cycle as Cn, cycle capacity retention rate = Cn / C1, record the number of cycles when the cycle capacity retention rate drops to 80% SOH.
[0224] 3) Battery hot box safety test The battery cell is fully charged to the corresponding design upper limit voltage of 3.65V, and the battery cell is equipped with a clamp. The mass m1 of the battery cell at this time is recorded. The battery cell is placed in an incubator. The incubator starts to heat up from room temperature, and the temperature is increased at 2℃ / min to 100℃, and maintained for 1 hour. Then the temperature is increased at 5℃ / min, and maintained for 30 minutes every 5℃ until the battery cell fails (smoke or fire occurs when the valve is opened). The test is stopped, and the battery cell mass m2 is recorded at room temperature. 1-(m2 / m1) is the weight loss rate of the battery cell. The higher the weight loss rate of the battery cell, the more side reaction products that are easy to spray in the battery cell, and the worse the safety performance.
[0225] 4) High temperature cycle life At 60°C, the prepared battery was charged to 3.65 V at a constant current of 1 C, then charged at a constant voltage of 3.65 V until the current dropped to 0.05 C, and after standing for 5 min, discharged to 2.1 V at a constant current of 1 C. This was the first charge / discharge cycle of the battery, and the discharge capacity at this time was recorded as the discharge capacity of the first cycle of the battery (C1); repeat the above steps for the same battery, and the process capacity of the battery after the nth cycle (Cn), the capacity retention rate after n cycles = Cn / C1×100%. Record the number of cycles at which the cycle capacity retention rate is 80%.
[0226] Table 1
[0227] From the comparison of the embodiments and the comparative examples, it can be seen that, based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide is 1%-6%, the mass proportion of the chain carboxylic acid ester solvent is 5%-75%, and the degree of graphitization of the negative electrode active material is 90%-96%. The battery monomer can achieve a balance between fast charging performance, high temperature cycle life and safety performance.
[0228] Table 2
[0229] From the comparison between Example 1 and Example 8, it can be seen that one electrode ear is formed in each layer of the positive electrode sheet of the battery cell, which is beneficial to improving the fast charging cycle life of the battery cell.
[0230] Table 3
[0231] From the comparison between Examples 1 and 9, it can be seen that when the porosity of the isolation membrane is 30%-42%, it is beneficial to improve the fast charging cycle life of the battery cell.
[0232] Table 4
[0233] From the comparison between Examples 1 and 10, it can be seen that when the thickness of the aluminum foil is 11 μm-14 μm, it is beneficial to improve the fast charging cycle life of the battery cell.
[0234] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A battery cell, characterized in that: It includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator disposed between the positive electrode sheet and the negative electrode sheet; The electrolyte includes a solvent and an electrolyte salt, wherein the electrolyte salt includes lithium bis(fluorosulfonyl)imide, and the mass proportion of the lithium bis(fluorosulfonyl)imide is 1%-6% based on the total mass of the electrolyte; The solvent includes a chain carboxylate solvent, and based on the total mass of the electrolyte, the mass proportion of the chain carboxylate solvent is 5%-75%; The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector, the negative electrode film layer includes a negative electrode active material, and the graphitization degree of the negative electrode active material is 90%-96%; The positive electrode plate comprises a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector. The positive electrode current collector comprises an aluminum foil, and the thickness of the aluminum foil is 10 μm-16 μm.
2. The battery cell according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the lithium bis(fluorosulfonyl)imide is 1.5%-5%.
3. The battery cell according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass of the chain carboxylate solvent accounts for 10%-65%.
4. The battery cell according to claim 1, characterized in that: The graphitization degree of the negative electrode active material is 92%-95%.
5. The battery cell according to claim 1 or 2, characterized in that: Based on the total mass of the electrolyte salt in the electrolyte, the mass proportion of the bis(fluorosulfonyl)imide lithium is 10%-50%.
6. The battery cell according to claim 1, characterized in that: The chain carboxylic acid ester solvent includes one or more of ethyl acetate, methyl acetate, methyl formate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, propyl butyrate, butyl butyrate, isopropyl acetate, and isoamyl acetate.
7. The battery cell according to claim 6, characterized in that: The chain carboxylate solvent includes one or more of ethyl acetate and methyl acetate. Based on the total mass of the solvent, the total mass of ethyl acetate and methyl acetate accounts for 5%-80%.
8. The battery cell according to claim 7, characterized in that: Based on the total mass of the solvent, the total mass of ethyl acetate and methyl acetate accounts for 10%-70%.
9. The battery cell according to claim 6, characterized in that: The chain carboxylate solvent includes methyl acetate, and the mass content of methyl acetate is 5%-80% based on the total mass of the solvent.
10. The battery cell according to claim 9, characterized in that: Based on the total mass of the solvent, the mass content of methyl acetate is 5%-50%.
11. The battery cell according to claim 9, characterized in that: Based on the total mass of the solvent, the mass content of methyl acetate is 10%-40%.
12. The battery cell according to claim 1, characterized in that: The solvent further includes a carbonate solvent, and the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
13. The battery cell according to claim 1, characterized in that: The solvent comprises ethylene carbonate, and the mass content of ethylene carbonate is 15%-35% based on the total mass of the solvent.
14. The battery cell according to claim 1, characterized in that: The solvent comprises dimethyl carbonate, and the mass content of dimethyl carbonate is 5%-50% based on the total mass of the solvent.
15. The battery cell according to claim 1, characterized in that: The negative electrode current collector includes copper foil, and the thickness of the copper foil is 4 μm-6 μm.
16. The battery cell according to claim 15, characterized in that: The copper foil has a thickness of 4 μm-5 μm.
17. The battery cell according to claim 1, characterized in that: The negative electrode sheet satisfies at least one of the following conditions: (1) The single-side density of the negative electrode film layer is 0.08g / 1540.25mm 2 -0.20 g / 1540.25 mm 2 ; (2) The compaction density of the negative electrode sheet is 1.2 g / cm 3 -1.9 g / cm 3 ; (3) The average thickness of the negative electrode film layer on one side is 30 μm to 150 μm; (4) The porosity of the negative electrode sheet is 20%-60%.
18. The battery cell according to claim 17, characterized in that: The negative electrode sheet satisfies at least one of the following conditions: (1) The single-side density of the negative electrode film layer is 0.10 g / 1540.25 mm 2 -0.16 g / 1540.25 mm 2 ; (2) The compaction density of the negative electrode sheet is 1.2 g / cm 3 -1.65 g / cm 3 ; (3) The average thickness of the negative electrode film layer on one side is 30 μm to 80 μm; (4) The porosity of the negative electrode sheet is 25%-40%.
19. The battery cell according to claim 1, characterized in that: The thickness of the aluminum foil is 11 μm-14 μm.
20. The battery cell according to claim 1, characterized in that The positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate and a modified material thereof.
21. The battery cell according to claim 1, characterized in that: The porosity of the isolation membrane is 25%-55%.
22. The battery cell according to claim 21, characterized in that: The porosity of the isolation membrane is 28%-42%.
23. The battery cell according to claim 21, characterized in that: The porosity of the isolation membrane is 30%-42%.
24. The battery cell according to claim 1, characterized in that The Gurley value G of the isolation membrane is 50s-620s, and the Gurley value refers to the time required for 100 mL of air to pass through 1 square inch of the isolation membrane under a pressure of 1.22 kPa when the isolation membrane is placed in an air permeability tester, and the unit is s.
25. The battery cell according to claim 24, characterized in that: The Gurley value G of the isolation film is 300s-610s.
26. The battery cell according to any one of claims 21 to 25, characterized in that: The separator includes a base film and a ceramic coating, and the ceramic coating is only disposed on the positive electrode side of the base film.
27. The battery cell according to claim 26, characterized in that: The ceramic coating comprises ceramic particles, and the ceramic particles comprise one or more of aluminum oxide, boehmite, silicon oxide, titanium oxide, magnesium oxide, calcium oxide, zinc oxide, zirconium oxide, and tin oxide.
28. The battery cell according to claim 27, characterized in that: The ceramic particles include one or more of alumina and boehmite.
29. The battery cell according to claim 26, characterized in that: The ceramic coating further comprises a binder, and the binder comprises one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, water-soluble unsaturated resin SR-1B, water-based acrylic resin, polyacrylamide, and polyvinyl alcohol.
30. The battery cell according to claim 29, characterized in that The binder includes polyvinylidene fluoride.
31. The battery cell according to claim 1, characterized in that The battery cell comprises a wound cell, the negative current collector comprises a negative current collecting portion and a negative electrode tab disposed on at least one side of the negative current collecting portion, and at least one circle of the negative electrode sheet of the wound cell comprises at least two negative electrode tabs.
32. The battery cell according to claim 1, characterized in that The battery cell comprises a wound cell, the positive current collector comprises a positive current collecting portion and a positive electrode tab disposed on at least one side of the positive current collecting portion, and at least one circle of the positive electrode sheet of the wound cell comprises at least two positive electrode tabs.
33. The battery cell according to claim 32, characterized in that: The wound battery cell includes a large surface area and a bending area, and the positive electrode tab is arranged in the large surface area of the wound battery cell. The number of layers of the positive electrode sheets in the wound battery cell is defined according to the rule that the number of positive electrode sheet layers in the large surface area increases successively along the winding direction from the inside to the outside. The positive electrode sheets of the wound battery cell have at least two consecutive layers, each of which is provided with a positive electrode tab.
34. The battery cell according to claim 1, characterized in that The liquid injection coefficient of the battery monomer is 2.5g / Ah-3.2g / Ah.
35. The battery cell according to claim 34, characterized in that: The liquid injection coefficient of the battery cell is 2.8 g / Ah-3.0 g / Ah.
36. A battery device, characterized in that: Comprising the battery cell according to any one of claims 1 to 35, the battery device comprises at least one of a battery module, a battery pack, and an energy storage battery.
37. An electrical device, characterized in that: A battery cell comprising any one of claims 1 to 35 or a battery device according to claim 36.
Citation Information
Patent Citations
Lithium ion secondary battery
CN118738569A
Secondary battery and electric device
CN118765451A
Electrochemical apparatus and electronic device
WO2024087068A1
Cited By
Battery cell, battery device and electric device
CN120048984A
Battery cell, battery device and electric device
CN120072863A
Battery cells, battery devices, and power-consuming devices
CN120072863B
Battery monomer, battery device, power utilization device and energy storage device
CN120072915A
Battery cell, battery device, and electric device
CN120072916A
